2014
DOI: 10.1208/s12248-014-9567-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Activity Cliffs Is Accompanied by Systematic Increases in Ligand Efficiency from Lowly to Highly Potent Compounds

Abstract: Abstract. Activity cliffs (ACs) are defined as pairs of structurally similar compounds sharing the same biological activity but having a large difference in potency. Therefore, ACs are often studied to rationalize structure-activity relationships (SARs) and aid in lead optimization. Hence, the AC concept plays an important role in compound development. For compound optimization, ligand efficiency (LE) represents another key concept. LE accounts for the relation between compound potency and mass. A major goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Third, SARI score was calculated for NNs as the raw structure–activity relationship (SAR) discontinuity score component of the SAR Index to quantify potency variations among NNs. For SARI score calculations, the Tanimoto similarity threshold for NNs was set to 0.6 and 0.4 for MACCS and ECFP4, respectively …”
Section: Methodsmentioning
confidence: 99%
“…Third, SARI score was calculated for NNs as the raw structure–activity relationship (SAR) discontinuity score component of the SAR Index to quantify potency variations among NNs. For SARI score calculations, the Tanimoto similarity threshold for NNs was set to 0.6 and 0.4 for MACCS and ECFP4, respectively …”
Section: Methodsmentioning
confidence: 99%
“…To further qualify 3D-cliff information, LE and LLE values were also calculated for compounds forming individual cliffs. If activity cliffs are a consequence of specific interactions and contributions to binding, rather than only increasing size or hydrophobicity of ligands, cliff formation should be accompanied by increases in LE and LLE, as has been shown previously (16). Of course, there are also specific lipophilic interactions that determine activity cliffs, which must be taken into consideration when judging about LLE values.…”
Section: Principles Of Hot Spot Analysismentioning
confidence: 73%
“…However, whether or not systematic trends might be detectable was an open question. The analysis revealed that the formation of 99.1% of all activity cliffs across different targets was accompanied by consistent increases in LE values between lowly and highly potent cliff partners, with, on average, ∆LE = 6.25 14 . For activity cliffs defined on the basis of calculated (molecular fingerprint-based) similarity values, comparable observations were made 14 .…”
Section: Ligand Efficiency and Lipophilic Efficiencymentioning
confidence: 96%
“…In a recent analysis 14 , 18,208 activity cliffs were extracted from more than 41,000 unique ChEMBL 15 (release 15) compounds with activity against the current spectrum of human targets. Then, differences in LE between lowly and highly potent cliff partners were systematically assessed.…”
Section: Ligand Efficiency and Lipophilic Efficiencymentioning
confidence: 99%
See 1 more Smart Citation